2019
DOI: 10.1039/c9ra04009a
|View full text |Cite
|
Sign up to set email alerts
|

Microgrooved collagen-based corneal scaffold for promoting collective cell migration and antifibrosis

Abstract: Microgrooved collagen membrane can effectively promote the epithelialization of corneal epithelial cells and inhibit the fibrosis of corneal stromal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 70 publications
3
12
0
Order By: Relevance
“…The L929 cells on the flat substrate appear in a strap-like shape, as Liu reported on a poly (vinyl alcohol)/poly (ethylene glycol) surface [ 44 ]. Cells cultured on the line array were oriented in alignment along the space formed between two struts, which was similar to the phenomena previously reported [ 45 ], appearing in a strip shape. When adhered to the ST scaffold with small pores and thin struts, the cells showed a less elongated and more spread-out microfilament cytoskeleton with many filopodia related to the strut ( Figure S2 ).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The L929 cells on the flat substrate appear in a strap-like shape, as Liu reported on a poly (vinyl alcohol)/poly (ethylene glycol) surface [ 44 ]. Cells cultured on the line array were oriented in alignment along the space formed between two struts, which was similar to the phenomena previously reported [ 45 ], appearing in a strip shape. When adhered to the ST scaffold with small pores and thin struts, the cells showed a less elongated and more spread-out microfilament cytoskeleton with many filopodia related to the strut ( Figure S2 ).…”
Section: Resultssupporting
confidence: 83%
“…between two struts, which was similar to the phenomena previously reported [45], appearing in a strip shape. When adhered to the ST scaffold with small pores and thin struts, the cells showed a less elongated and more spread-out microfilament cytoskeleton with many filopodia related to the strut (Figure S2).…”
Section: Modulation Of Cell Behavior On Different Microstructuressupporting
confidence: 90%
“…[ 1–5 ] However, traditional approaches mainly rely on functional biomaterials seeded with cells, supplemented with bioactive factors, or in situ recruitment of cells after transplantation. [ 6–9 ] These methods are insufficient to make a finely tuned complex milieu for providing multiscale 3D architectures, such as curved cornea with crisscross internal collagenous pattern or a chamber‐shaped helical cardiac chambers.…”
Section: Introductionmentioning
confidence: 99%
“…The drugs like steroids, hormones, antibiotics can be loaded onto the films by hydrogen bonding, covalent bonding or simply by entrapment [50]. Such films can be used for the treatment of corneal tissue infections [53], liver cancer etc. In one of the studies, the collagen films loaded with BMPs have shown direct osteoinduction without the formation of cartilage when placed in close contact with osteogenic cells [54].…”
Section: Collagen Filmsmentioning
confidence: 99%
“…Its mechanical properties can be improved by crosslinking and composting. To maintain corneal transparency, micropatterned collagen scaffolds have been reported which can regulate cellular behaviour [53]. The source and age of collagen play a significant role in the final physical properties of scaffolds like the structure, optical properties, biocompatibility, etc.…”
Section: Corneal Tissue Engineeringmentioning
confidence: 99%